Uso da Moringa oleifera lam. como biossorvente do cádmio em águas. - Santana, Pedro Manoel Araujo de (2017)
Industrial processes have historically been an important factor in environmental degradation. Improper disposal of industrial waste containing potentially toxic metals in water supplies is a major physical, biotic and anthropic problem. The objective of this study was to evaluate the adsorptive capacity of the ground seeds of Moringa oleifera Lam. As an alternative material to synthetic biosorbents for removal of cadmium ions in water. Before and after the treatments were carried out chemical analysis according to official methodology. The results were analyzed by ANOVA and Pearson table chart with a significance level of 5% and correlation between variables. The results showed a better performance of the alternate method, employing pitcher for removing cadmium in water treatment under the following conditions: slightly basic pH (7.11); Contact time between pitcher and water was six hours; moringa one gram per liter of water. Under these conditions there was a reduction in the concentration of 70.28% cadmium proving that the alternative methodology in addition to being inexpensive, easy to perform, helps to minimize severe impacts that metal brings to people's health and the environment.